ANALISIS PERBANDINGAN SEBELUM DAN SESUDAH PENGENAAN TARIF PAJAK PROGRESIF PADA KENDARAAN BERMOTOR BERDASARKAN â€œTHE FOUR MAXIMSâ€ DI KOTA MANADO - Rosalie, Eugenia; Tinangon, Jantje; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Motor vehicle tax is one source of revenue that provides kontirbusi important. With the entry into force of a progressive tax on motor vehicles beginning in 2012 based on Law No. 28 of 2009 on Regional Taxes and Levies as well as the North Sulawesi Provincial Regulation No. 7 of 2011 on Local Taxes North Sulawesi province that both private vehicle ownership and tax rates set forth progressively. At the beginning of the adoption of the progressive tax, many people who feel uncomfortable and overwhelmed, perhaps this was due to lack of information regarding the application of progressive rates. The purpose of this study is how the progressive tariffs on motor vehicles based principle of taxation in the city of Manado, and determine the impact of comparing before and after imposition. The method used is descriptive analytical method, which is a research method to reveal the existing problems in office administration, data processing, analyzing, researching and interpret and make conclusions and give suggestions which are then arranged in a systematic discussion so that problems that exist in the company can be understood. From the results of the research can be seen still highly progressive taxation in accordance with "The Four Maxims" that principle of taxation proposed by Adam Smith which consists of similarity and balance (Equality), legal certainty (certainty), (c) a timely basis (convenient of payment), and (d) the principle of economies of collection. progressive taxation has other positive effects which increase the acceptance of PKB and BBNKB which automatically increases the acceptance of the PAD that most of it is the source of Local Taxes. Imposition of Tax Rate has been running as a Progressive government enforce the original purpose and is in accordance with the tax function is budgetair function.